2008
DOI: 10.1111/j.1365-2702.2008.02536.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurse prescribers’ interactions with and perceptions of pharmaceutical sales representatives

Abstract: Appropriate use of pharmaceutical sales representatives' services may enhance the ability of nurse prescribers to deliver optimal nursing care. Methods, such as counter-detailing may be necessary to maintain an evidence-based approach as the controlling factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Thirty-six percent ( n =  33/92) of a convenience sample of US nurse prescribers in 2009 reported that sales representatives suggested some form of compensation (food or gifts) in exchange for preferential prescription of their product [35]. Among a random sample of family NPs ( n =  84) in 2009, those who were less critical of the practice of receiving gifts from industry accepted gifts more frequently ( r  = −0.48, p <0.0001) [34].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirty-six percent ( n =  33/92) of a convenience sample of US nurse prescribers in 2009 reported that sales representatives suggested some form of compensation (food or gifts) in exchange for preferential prescription of their product [35]. Among a random sample of family NPs ( n =  84) in 2009, those who were less critical of the practice of receiving gifts from industry accepted gifts more frequently ( r  = −0.48, p <0.0001) [34].…”
Section: Resultsmentioning
confidence: 99%
“…Although clinicians expressed a range of attitudes toward industry interactions, only a minority held negative views of industry; most clinicians across disciplines held favorable views of interactions with sales representatives and of industry interactions in general. The majority of a convenience sample of US nurse prescribers in 2009 described sales representatives as friendly and sociable (97%; n =  89/92), professional (89.1%; n =  82/92), and knowledgeable about their product (88%; n =  81/92) [35]. About half ( n =  869/1,640) of a nationally representative sample of US pharmacists in 2005 endorsed an overall positive perception of the pharmaceutical industry, and half ( n =  853/1,640) disagreed with the statement that representatives were of little value to pharmacists [40].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations